2016
DOI: 10.1055/s-0036-1579635
|View full text |Cite
|
Sign up to set email alerts
|

Fibrinogen Is at the Interface of Host Defense and Pathogen Virulence in Staphylococcus aureus Infection

Abstract: Fibrinogen not only plays a pivotal role in hemostasis but also serves key roles in antimicrobial host defense. As a rapidly assembled provisional matrix protein, fibrin(ogen) can function as an early line of host protection by limiting bacterial growth, suppressing dissemination of microbes to distant sites, and mediating host bacterial killing. Fibrinogen-mediated host antimicrobial activity occurs predominantly through two general mechanisms, namely, fibrin matrices functioning as a protective barrier and f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
93
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 78 publications
(98 citation statements)
references
References 174 publications
(207 reference statements)
2
93
0
3
Order By: Relevance
“…ClfB appears to recognize a glycine and serine rich motif, GSSGXGXXG, that is also present in loricrin, explaining how it is able to bind to several different ligands with similar affinities (Mulcahy et al, 2012; Xiang et al, 2012). Of note, mouse fibrinogen lacks this motif, explaining why ClfB binds to human fibrinogen with higher affinity (Ko and Flick, 2016). Studies in both mice and humans have shown that ClfB is important for nasal colonization (Schaffer et al, 2006; Wertheim et al, 2008), and this appears to be primarily due to its ability to bind loricrin (Mulcahy et al, 2012).…”
Section: Fibrinogen/fibrin Mediated Clumpingmentioning
confidence: 99%
See 4 more Smart Citations
“…ClfB appears to recognize a glycine and serine rich motif, GSSGXGXXG, that is also present in loricrin, explaining how it is able to bind to several different ligands with similar affinities (Mulcahy et al, 2012; Xiang et al, 2012). Of note, mouse fibrinogen lacks this motif, explaining why ClfB binds to human fibrinogen with higher affinity (Ko and Flick, 2016). Studies in both mice and humans have shown that ClfB is important for nasal colonization (Schaffer et al, 2006; Wertheim et al, 2008), and this appears to be primarily due to its ability to bind loricrin (Mulcahy et al, 2012).…”
Section: Fibrinogen/fibrin Mediated Clumpingmentioning
confidence: 99%
“…The sdrE isoform is more common and is found in ~55–65% of clinical isolates (Li et al, 2013; Peacock et al, 2002; Yu et al, 2012). The function of SdrE is less clear, although preliminary results suggest that it also binds fibrinogen, with a higher affinity for non-human fibrinogen (Ko and Flick, 2016). In addition, SdrE has been reported to bind to complement regulator factor H (Sharp et al, 2012), and it can also promote platelet aggregation (O’Brien et al, 2002a).…”
Section: Fibrinogen/fibrin Mediated Clumpingmentioning
confidence: 99%
See 3 more Smart Citations